Growth Patterns of Oxyeleotris marmorata from the Toba Lake, Haranggaol District, Simalungun Regency, Sumatera Utara Province - Sander Jaya Aritonang; Deni Efizon; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPopulation of Oxyeleotris marmorata in the Toba Lake, Sumatera Utara Province is relatively high and it  indicates that the lake environment is suitable for the life of the fish. To understand the biological aspects, a study has been carried out from May to June 2019. The fish was captured around the fish culture area. There were 26 morphological characters measured. The number of fish captures was 64 (19.1-35.1 cm PT and 79-594 gr BB). There were 7 morphometricl characteristic differences in female and male O. marmorata. In female, the distance between the mouth to the pectoral fin and the length of base pectoral fin is shorter than that of the male.  The length-weight relationship in O. marmorata was negatively allometric ( b  was 2.818 in female and 2.69 in male). Keywords:    Culture Area, Allometric Negative, Isometric, Morphological Characteristics